Contemporary Challenges of Legal Psychology: Interdisciplinary and Interagency Collaboration - V.G. Bulygina (Психология и право, 2025)
We present to your attention a new thematic issue of our journal. The theme of the issue is “Modern challenges of legal psychology: interdisciplinary and interdepartmental interaction”.